Nanoengineered Gallium Ion Incorporated Formulation for Safe and Efficient Reversal of PARP Inhibition and Platinum Resistance in Ovarian Cancer - Li Yangyang; Cen Yixuan; Tu Mengyan; Xiang Zhenzhen; Tang Sangsang; Lu Weiguo; Zhang Hongbo; Xu Junfen (American Association for the Advancement of Science, 2025)
Platinum-based chemotherapy remains the main systemic treatment of ovarian cancer (OC). However, the inevitable development of platinum and poly (adenosine diphosphate-ribose) polymerase inhibitor (PARPi) resistance is associated with poor outcomes, which becomes a major obstacle in the management of this disease. The present study developed "all-in-one" nanoparticles that contained the PARPi olaparib and gallium (Ga) (III) (olaparib-Ga) to effectively reverse PARPi resistance in platinum-resistant A2780-cis and SKOV3-cis OC cells and in SKOV3-cis tumor models. Notably, the olaparib-Ga suppressed SKOV3-cis tumor growth with negligible toxicity. Moreover, the suppression effect was more evident when combining olaparib-Ga with cisplatin or carboplatin, as evaluated in A2780-cis and SKOV3-cis cells. Mechanistically, the combined treatment induced DNA damage, which elicited the activation of ataxia telangiectasia mutated (ATM)/AMT- and Rad3-related (ATR) checkpoint kinase 1 (Chk1)/Chk2 signal transduction pathways. This led to the arrest of cell cycle progression at S and G2/M phases, which eventually resulted in apoptosis and cell death due to unrepairable DNA damage. In addition, effective therapeutic responses to olaparib-Ga and cisplatin combination or olaparib-Ga and carboplatin combination were observed in SKOV3-cis tumor-bearing animal models. Altogether, the present findings demonstrate that olaparib-Ga has therapeutic implications in platinum-resistant OC cells, and the combination of olaparib-Ga with cisplatin or carboplatin may be promising for treating patients with OC who exhibit resistance to both PARPi and platinum.